Survival of cervical cancer patients at Moi teaching and Referral Hospital, Eldoret in western Kenya - E. Mwaliko; P. Itsura; A. Keter; Dirk De Bacquer; N. Buziba; H. Bastiaens; A. Jackie; A. Obala; V. Naanyu; P. Gichangi; M. Temmerman (BMC Cancer, 2023)
Abstract Background Cervical cancer is a major health burden and the second most common cancer after breast cancer among women in Kenya. Worldwide cervical cancer constitutes 3.1% of all cancer cases. Mortality rates are greatest among the low-income countries because of lack of awareness, screening and early-detection programs and adequate treatment facilities. The main aim was to estimate survival and determine survival predictors of women with cervical cancer and limited resources in western Kenya. Methods Retrospective charts review of women diagnosed with cervical cancer and follow-up for two years from the date of the histologic diagnosis. The outcome of interest was death or survival at two years. Kaplan Meier estimates of survival, log-rank test and Cox proportional hazards regression were used in the survival analysis. Results One hundred and sixty-two (162) participants were included in the review. The median duration was 0.8 (interquartile range (IQR) 0.3, 1.6) years. The mean age at diagnosis was 50.6 years (SD12.5). The mean parity was 5.9 (SD 2.6). Fifty percent (50%) did not have health insurance. Twenty six percent (26%) used hormonal contraceptives, 25.9% were HIV positive and 70% of them were on anti-retroviral treatment. The participants were followed up for 152.6 person years. Of the 162 women in the study, 70 (43.2%) died giving an overall incidence rate (IR) of 45.9 deaths per 100 person years of follow up. The hazard ratios were better for the patients who survived (0.44 vs 0.88, p-value < 0.001), those who had medical insurance (0.70 vs 0.48, p-value = 0.007) and those with early stage at diagnosis (0.88 vs 0.39, p-value < 0.001). Participants who were diagnosed at late stage of the disease according to the International Federation of Gynecology and Obstetrics staging for cervical cancer (FIGO stage 2B-4B) had more than eight times increased hazard of death compared to those who were diagnosed at early stage (1-2A): Hazard Ratio: 8.01 (95% CI 3.65, 17.57). Similarly, those who underwent surgical management had 84% reduced hazard of mortality compared to those who were referred for other modes of care: HR: 0.16 (95% CI: 0.07, 0.38). Conclusion Majority of the participants were diagnosed late after presenting with symptoms. The 1 and 2-year survival probability after diagnosis of cervical cancer was 57% AND 45% respectively. It is imperative that women present early since surgery gives better prognosis or better still screening of all women prioritized.